Influence of Ecto-nucleoside triphosphate diphosphohydrolase activity on Trypanosoma cruzi infectivity and virulence. - Ramon F Santos; Marcela A S Pôssa; Matheus S Bastos; Paulo M M Guedes; Márcia R Almeida; Ricardo Demarco; Sergio Verjovski-Almeida; Maria T Bahia; Juliana L R Fietto (Public Library of Science (PLoS), 2009)
BACKGROUND: The protozoan Trypanosoma cruzi is the causative agent of Chagas disease. There are no vaccines or effective treatment, especially in the chronic phase when most patients are diagnosed. There is a clear necessity to develop new drugs and strategies for the control and treatment of Chagas disease. Recent papers have suggested the ecto-nucleotidases (from CD39 family) from pathogenic agents as important virulence factors. In this study we evaluated the influence of Ecto-Nucleoside-Triphosphate-Diphosphohydrolase (Ecto-NTPDase) activity on infectivity and virulence of T. cruzi using both in vivo and in vitro models. METHODOLOGY/PRINCIPAL FINDINGS: We followed Ecto-NTPDase activities of Y strain infective forms (trypomastigotes) obtained during sequential sub-cultivation in mammalian cells. ATPase/ADPase activity ratios of cell-derived trypomastigotes decreased 3- to 6-fold and infectivity was substantially reduced during sequential sub-cultivation. Surprisingly, at third to fourth passages most of the cell-derived trypomastigotes could not penetrate mammalian cells and had differentiated into amastigote-like parasites that exhibited 3- to 4-fold lower levels of Ecto-NTPDase activities. To evidence the participation of T. cruzi Ecto-NTPDase1 in the infective process, we evaluated the effect of known Ecto-ATPDase inhibitors (ARL 67156, Gadolinium and Suramin), or anti-NTPDase-1 polyclonal antiserum on ATPase and ADPase hydrolytic activities in recombinant T. cruzi NTPDase-1 and in live trypomastigotes. All tests showed a partial inhibition of Ecto-ATPDase activities and a marked inhibition of trypomastigotes infectivity. Mice infections with Ecto-NTPDase-inhibited trypomastigotes produced lower levels of parasitemia and higher host survival than with non-inhibited control parasites. CONCLUSIONS/SIGNIFICANCE: Our results suggest that Ecto-ATPDases act as facilitators of infection and virulence in vitro and in vivo and emerge as target candidates in chemotherapy of Chagas disease.